Penca Existence among the Sundanese - Yuniadi, Agusmanon; Lubis, Nina Herlina; Zakaria, Mumuh Muhsin (Universitas Pendidikan Indonesia, 2018)
ABSTRACT: â€œMaenpoâ€ is one of the pillars of culture so as to be one of the elements forming the character society in Cianjur, West Java, besides â€œngaosâ€ and â€œmamaosâ€. â€œMaenpoâ€ is one of a stream of traditional martial arts that prefer the flavor, rather than physical violence. The flavors here means toying his opponents with the power of its moves, so that the opponents became frustrated. In this article will explain how the process of â€œmaenpoâ€ development since the Netherlands colonial rule until the Republic of Indonesia. For answers to that question, in the article used the method of history that consists of four steps, namely: heuristics, critique, interpretation, and historiography. The results of this study show that at the beginning of its development, â€œmaenpoâ€ grown in limited circumstances, namely the circle up (noblemen) of Sunda and Islamic boarding school. The â€œmenakâ€ (noblemen) of Cianjur mastered the â€œmaenpoâ€ not to be champions, but rather as one way of sharpening the ability it feels in understanding their relationship with God and his social environment. Also in the Islamic boarding schoolsâ€™ environment, â€œmaenpoâ€'s training as a means of developing the control of lust. Nevertheless, the development of â€œmaenpoâ€ relatively faster in the Islamic boarding schools environment compared to among the â€œmenakâ€ of Sunda in West Java, Indonesia.KEY WORD: Maenpo; Cianjur Regency; Sundanese Noblemen; Islamic boarding school; Cultivate a Sense.Â ABSTRAKSI: â€œKeberadaan Penca di Antara Orang Sundaâ€. â€œMaenpoâ€ merupakan salah satu pilar budaya sehingga menjadi salah satu unsur pembentuk karakter masyarakat di Cianjur, Jawa Barat, selain â€œngaosâ€ dan â€œmamaosâ€. â€œMaenpoâ€ merupakan salah satu aliran seni bela diri tradisional yang lebih mengutamakan rasa, bukan kekerasan fisik. Rasa di sini berarti mempermainkan lawan dengan kekuatan jurus-jurusnya, sehingga lawan menjadi frustasi. Dalam artikel ini akan dijelaskan bagaimana proses perkembangan â€œmaenpoâ€ sejak masa penjajahan Belanda hingga masa Republik Indonesia. Untuk memperoleh jawaban atas pertanyaan, dalam artikel ini digunakan metode sejarah yang terdiri dari empat tahapan, yaitu: heuristik, kritik, interpretasi, dan historiografi. Hasil kajian ini menujukan bahwa pada awal perkembangannya, â€œmaenpoâ€ tumbuh di lingkungan terbatas, yakni kalangan â€œmenakâ€ dan pesantren. Para â€œmenakâ€ Cianjur menguasai â€œmaenpoâ€ bukan untuk menjadi jawara, melainkan sebagai salah satu cara mengasah kemampuan rasa dalam memahami hubungan mereka dengan Tuhan dan lingkungan sosialnya. Juga di lingkungan pesantren, â€œmaenpoâ€ berkembang sebagai sarana pelatihan pengendalian hawa nafsu. Meskipun demikian, perkembangan â€œmaenpoâ€ relatif lebih cepat di lingkungan pesantren dibandingkan dengan di kalangan â€œmenakâ€ Sunda di Jawa Barat, Indonesia.KATA KUNCI: Maenpo; Kabupaten Cianjur; Menak Sunda; Pesantren; Mengolah Rasa.Â Â Â Â About the Authors: Agusmanon Yuniadi is a Student of Doctoral Program at the Graduate School of Humanities Studies UNPAD (Padjadjaran University) Bandung, West Java, Indonesia. Prof. Dr. Nina Herlina Lubis and Dr. Mumuh Muhsin Zakaria are the Lecturers at the Department of History and Philology, Faculty of Humanities UNPAD Bandung. Authors correspondence: agusmanon@unpad.ac.id Suggested Citation: Yuniadi, Agusmanon, Nina Herlina Lubis Mumuh Muhsin Zakaria. (2018). â€œPenca Existence among the Sundaneseâ€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Volume 3(2), September, pp.103-112. Bandung, Indonesia: UPI [Indonesia University of Education] Press, ISSN 2527-3868 (print) and 2503-457X (online). Article Timeline: Accepted (July 3, 2018); Revised (August 17, 2018); and Published (September 30, 2018).